Remote tutoring of pre-service EFL teachers using iPads. (21st August 2018) - Allen, Christopher; Hadjistassou, Stella
Abstract: With the availability of portable and relatively inexpensive audiovideo recording devices in the form of iPads and other mobile technologies in combination with increasing bandwidth, the remote observation and training of pre-service EFL student teachers without the physical presence of a tutor in the classroom is now a viable proposition. This paper reports on a novel initiative to provide remote feedback to a group of primary EFL pre-service teachers on teaching practice placement in Africa from a tutor based in Sweden via iPad minis and the training institution's Moodle virtual learning environment. The feedback was assessed in relation to the Cambridge English Teaching Framework. Results suggest that the combination of recorded audiovideo material during the pre-service teachers' teaching practice and Moodle feedback from the remote tutor can provide a valuable basis for tutorial support, formative assessment, and reflection for student EFL teachers on teaching practice.